Connecting South-South Communities: A Narrative of South Africa-Malaysia Relations - Danial Yusof, (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2020)
While introducing critical theory in international relations (IR), Marcos Farias Ferreira referred to the works of the radical IR scholar, Robert W. Cox. In it he posits that unlike the realist approach, critical theory views IR not be in isolation from social forces. There is a need to view global politics (here I would suggest that this applies to comparative politics and area studies as well) as a construct that evolves through the complexity of state, sub-state, trans-state forces in economic, cultural and ideological spheres i.e. a combination of the material and ideational in acquiring legitimacy, emancipation and political order. The author of this book adopts this approach.